Androgen Insensitivity Syndrome: A Case Report - Islam, Sardar Rezaul; Paul, Debabrata; Sarkar, Shah Alam (British Journal of Healthcare and Medical Research, 2025)
A 22 years old married woman presented with bilateral Inguinal hernia. She gave history of primary amenorrhea and primary infertility. She had well developed breast but scanty pubic hair, no axillary hair and normal looking female external genitalia. Ultra sound revealed absence of uterus, short vagina and bilateral inguinal hernia with inguinal testes. Her Serum testosterone level was elevated. Bilateral orchiectomy and hernia repair was done. Her chromosomal analysis revealed 46 XY. It was confirmed that this was case of Complete variety of Androgen Insensitivity Syndrome (CAIS).